Trabalho e sentido para empregados (as) longevos (as) dos bancos públicos: uma proposta de leitura fenomenológico-existencial. - Teixeira, Zirlana Menezes (2020)
The interest in the mental health of the worker under the perspective of longevity needs to be intensified in the face of the growing increase in life expectancy in Brazil. It is estimated that by the year 2050, thirty percent of the population will be sixty years old or older. Investigating the reception in the psychological clinic for this age group of workers, we sought to know some elements that can sustain their well-being and understand the meanings attributed to work by long-lived workers. For the purposes of this research, it was decided to study the Brazilian banking segment, specifically that of public banks, focusing on long-lived bankers from a public bank, who acquired the right to retire, but remained developing its activities in the corporate environment. For this understanding, in the phenomenological-existential perspective, conceptions about work, meaning and professional activity are developed; the professional activity of the bank is characterized and it is investigated how the construction of meanings of work occurs for the long-term bankers of a public bank. The research was qualitative in nature with a phenomenological-existential approach based on Hannah Arendt and Viktor Frankl. In this study, six bank employees aged over sixty who still carry out their activities in a public bank participated in a narrative interview, whose data treatment was carried out according to the Amedeo Giorgi Meaning Unit model. The essential constituents of the sense of work identified were living with generations; self-image and activity performed; interpersonal relationship; strengthening the image of oneself before others; retirement expectation; and, technology. The study favored, in addition to reflection and theoretical deepening of the central guiding themes in the field of work psychology, the development of a clinical action outline aimed at people aged sixty or over and who remain active in the corporate labor market.